Structural and Dielectric Properties of Two Different BaTiO3/Polyaniline Nanocomposites - ESMER, KADİR; MADAKBAŞ, SEYFULLAH (SPRINGER, 2013)
Barium titanium oxide/polyaniline (BaTiO3/PANI) nano-composites were obtained in two different processes by the use of PANI and BaTiO3 nano-particles synthesized by the sol-gel technique. FT-IR, XRD, SEM and TGA measurements were taken for structural properties of all samples. The molecular interaction between BaTiO3 nanoparticles and PANI was between the H atoms in the N-H bond and the OH molecules in the solution environment. The said interaction was coordinated with BaTiO3 molecules over O atoms. XRD results confirmed that the synthesized BaTiO3 had a characteristic cubic perovskite structure and that its structure had not changed. TGA results revealed that the composites became more stable as the BaTiO3 amount increased. The dielectric measurement results are consistent with the structural results at higher frequencies. Dielectricity increased as BaTiO3 ratio increased in the environment. The change in the real part of the dielectric permittivity by frequency was stable at high frequencies. According to these results, it is concluded that the composite samples could have very high electromagnetic wave absorption values at higher frequencies (GHz).
Keywords: BaTiO3; Polymer; Composite; Dielectric properties; FABRICATION; FILMS